Localised right upper-lobe pulmonary oedema caused by extension of giant cell carcinoma to the mitral valve - Ono, A (The British Institute of Radiology., 2011)
Giant cell carcinoma of the lung is a very rare primary malignant tumour and localised right upper-lobe pulmonary oedema is also unusual. We report a case of giant cell carcinoma, which invaded the left atrium through the left pulmonary vein and caused localised right upper-lobe pulmonary oedema.